#TITLE_ALTERNATIVE# - DWISAPUTRA (NIM : 23215075), INDRA
Batch distillation column has time delay characteristics in output response and nonlinear time variant. The FLC controller is designed and implemented on batch column distillation. PID controller is used as a comparison of FLC's ability to overcome plant characteristics. Distilation experiments have been done by ethanol and water separation. Initial mass hold up is 30% ethanol with water solvent. Setpoint is set at 80% concentration. Ziegler Nichols method is used to determine the value of P, I and D gains for PI and PID controllers. Several schemes were created to compare the performance of PI, PID and FLC. PID controller used difference gain depending on the oscillation period of the scheme. The FLC design uses different inputs depending on to the cases also. The scheme with the linear plant condition has been simulated on Simulink Matlab. PID shown better results then PI and FLC using linearized plant. Scheme with nonlinear conditions and delay plant has been implemented in mini plant batch distillation column Honeywell. FLC show better then PI, PID to overcome delay time and nonlinearity. The scheme comparing the capabilities of each controller in getting the volume distilation product has been compared also. FLC produced more product in volume.